Koordinasi Simpang APILL pada Simpang Sulfat dan Simpang Ciliwung Kecamatan Blimbing Kota Malang - Ihsan, Rizki Muhammad; Supriyanto, Bambang (Universitas Batanghari Jambi, 2025)
Sulfat signalized intersection and Ciliwung signalized intersection is one of the road sections on Jalan Sunandar Priyo Sudarmo, Malang City. Sulfat signalized intersection and Ciliwung signalized intersection have a distance of 270 meters and are signalized intersections that have not been coordinated because they have different cycle times. The existing cycle time at Sulfat signalized intersection is 122 seconds and at Ciliwung signalized intersection is 83 seconds. During peak hours, delays and vehicle queues occur at these two signalized intersections. The purpose of this study is to analyze the performance of the two signalized intersections in existing conditions, coordinate the two intersections so that there is an increase in performance and performance analysis in the coming year. The method used in this research is to use the form in the Indonesian Road Capacity Guidelines Year 2023. The results obtained show that Sulfat signalized intersection has a degree of saturation of 0.89 with level of service E and Ciliwung signalized intersection has a degree of saturation of 1.34. Alternative planning results show Sulfat signalized intersection produces a degree of saturation of 0.74 and a delay of 24.05 with level of service C and Ciliwung signalized intersection produces a degree of saturation of 0.8 and a delay of 23.83 with level of service C. A new cycle time was planned to coordinate the two intersections and the resulting cycle time was 68 seconds. The coordination of the signalized intersection resulted in a bandwidth of 23 seconds and 22 seconds. The performance of the coordinated signalized intersection in the next 5 years will decrease until it reaches level of service F.